Keluarga Selektif dan Komunikatif dalam Memilih Pasangan - Olis Wulandari; M. Wildan Razka R; Ahmad Mario M; Humaeroh (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Choosing a life partner is a crucial stage in an individual's life cycle that impacts long-term family harmony. This study aims to analyze the role of family communication patterns and levels of selectivity in the process of selecting a potential life partner. A qualitative case study approach was used, involving families actively involved in the matchmaking process or granting their blessings. The results indicate that communicative families, characterized by open dialogue between parents and children regarding values, life principles, and the purpose of marriage, tend to be more effective in selecting a partner. Selectivity based on shared values ​​(religion, culture, and life principles) and personality compatibility, supported by good communication, can reduce the risk of postmarital conflict.